1977
DOI: 10.1213/00000539-197701000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Improved Oxygenation During Thoracotomy with Selective PEEP to the Dependent Lung

Abstract: In 22 patients during thoracotomy in the lateral position, the effects of selective positive end-expiratory pressure (PEEP) to the dependent lung while simultaneously ventilating the non-dependent lung at zero end-expiratory pressure (ZEEP) on (1) inspired O2 concentration required to maintain adequate Pao2 during thoractomy and 2) alveolar-arterial oxygen difference (AaO2D) while breathing 100 percent O2 at the end of thoractomy were examined and compared to ventilation of both lungs at ZEEP, Selective PEEP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…From the test we gained interesting new insights. In agreement with Brown, et al (9), THT in Two-LV (PEEP +6 cmH2O) does not deteriorate oxygenation (PaO2 : 473.5 ! 69.4 vs. 469.9 !…”
Section: Discussionsupporting
confidence: 91%
“…From the test we gained interesting new insights. In agreement with Brown, et al (9), THT in Two-LV (PEEP +6 cmH2O) does not deteriorate oxygenation (PaO2 : 473.5 ! 69.4 vs. 469.9 !…”
Section: Discussionsupporting
confidence: 91%
“…Methods to improve oxygenation during 1‐lung ventilation and thoracoscopy need to be evaluated to minimize anesthetic risk to the patient. Such methods may include varying tidal volume, 20 continuous positive airway pressure (CPAP) to the nonventilated lung, 17,22 and the application of positive end‐expiratory pressure (PEEP) to the ventilated lung 18,28–31 …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the effect of PEEP should be determined and optimized by measuring DO 2 52 . DO 2 to peripheral tissues is determined by both CO and arterial oxygen content (CaO 2 ) 16,17,28–30,53 . If PEEP induces a significant reduction in CO that outweighs the gain in CaO 2 , the net results will be adverse for the patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying PEEP would help to splint the alveoli throughout the respiratory cycle and thus improve oxygenation. However, several studies on the effects of PEEP during OLV produced conflicting evidence, some showing improvement [12][13][14][15][16] and others no benefit or worsening of P a O 2 [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%